ЗАРУБІЖНИЙ ДОСВІД ЗДІЙСНЕННЯ ПРИВАТНОЇ ДЕТЕКТИВНОЇ ДІЯЛЬНОСТІ ТА ЙОГО АДАПТАЦІЯ В УКРАЇНІ - ЛИТВИНЕНКО, В. І. (SUPREMANCE OF LAW, 2016)
The article analyzes the conditions of work of private detectives in different countries. Particular attention is paid to the peculiarities of private detective activity in the UK, Germany, the United States, where private detectives have great opportunities, and in fact complement the law enforcement agencies. Examples of regulation of private detective activity in the Republic of Belarus and the Russian Federation are of interest due to the common historical past with Ukraine. Based on the analysis of foreign experience the author determines the conditions necessary for the full development of the domestic private detective activity.
Keywords: private detective work; law enforcement; data collection; security